The Mediation and the Role of Lawyers in the Procedure through the Prism of Bulgarian History - Nedeleva, Petya (Yearbook of the Law Department, 2019)
The possibility of resolving conflicts through alternative means is a favorable alternative for the parties, as it has deep roots in Bulgarian history, customs and law. If we turn to the history of Bulgarian law we will find that they are often used as an opportunity to resolve disputes of various kinds. Historically, Bulgarian rulers have personally participated in negotiations to resolve international conflicts – for example, Khan Krum proposed negotiations to avoid or end hostilities with Byzantium. The prince Boris I Michael also showed excellent negotiation skills when accepting Christianity as the state religion. During the Ottoman rule, such conciliatory functions were played by the bodies of the Bulgarian municipalities, the guild organizations and representatives of the spiritual authorities. After the Liberation, this tradition was the basis of the Elderly Judicial Councils, the amicable (conciliatory) courts, whose activity is based on the principles of voluntariness, reconciliation and reaching a mutually beneficial agreement.